Governança de stakeholders e sua inflûencia no desenvolvimento local - Freitas, Oziel Rodrigues de (2022)
Governance has been indispensable for the good development of contemporary society and has the purpose of bringing stakeholders together in order to form ideas for decision-making, thus contributing to local development. However, there is a need to investigate more deeply the relationship between public governance issues and stakeholders in the pursuit of development. In this way, the study contributes to measuring and concretizing the dimensions of public governance and local development. Thus, the objective of this study was to analyze the relationship between stakeholder governance and local development in the municipalities of Rio Grande do Sul (RS). The population analyzed consisted of counselors from the Regional Development Councils - RS (COREDE) and Municipal Secretaries. 570 respondents were sent between secretaries of the municipalities of RS and councilors of COREDE, with a return of 142 responses to the questionnaires sent, being that a return was obtained from 60 respondents from the executive, 70 respondents from civil society and 8 respondents from the legislature. For data analysis, the following statistical techniques were used (Descriptive Analysis, Factor Analysis and Regression), factorial analysis in this research was to highlight the predicted factors and regression was to correlate the factors studied. for data mining, it was done using SPSS 20.0® software. As a result of this research found some panoramas It can be concluded that in order to have a full Local Development it is necessary to have a Responsible Governance, Participatory Governance, Transparent Governance (advertising), Governance - Stakeholders and an Inclusive Governance.